Apocalypse now, apocalypse when? Economic growth and structural breaks in Argentina (1886–2003). Issue 1 (27th October 2021) - Campos, Nauro F.; Karanasos, Menelaos G.; Karoglou, Michail; Koutroumpis, Panagiotis; Zopounidis, Constantin; Christopoulos, Apostolos
Abstract: Argentina is the only country in the world that was developed in 1900 and developing in 2000. Although there is widespread consensus on the occurrence and uniqueness of this decline, an intense debate remains on its timing and underlying causes. This paper provides a first systematic investigation of the timing of the Argentine debacle. It uses an array of econometric tests for structural breaks and a range of GDP growth series covering 1886–2003. The main conclusion is the dating of two key structural breaks (in 1918 and 1948), which we argue support explanations for the debacle that highlight the slowdown of domestic financial development and trade protectionism (after 1918) and of institutional development (after 1948).